Ultrastructure of the intercellular space in adult murine ventricle revealed by quantitative tomographic electron microscopy - Leo-Macías, Alejandra (Cardiovasc Res, 2015)
AIMS: Progress in tissue preservation (high-pressure freezing), data acquisition (tomographic electron microscopy, TEM), and analysis (image segmentation and quantification) have greatly improved the level of information extracted from ultrastructural images. Here, we combined these methods and developed analytical tools to provide an in-depth morphometric description of the intercalated disc (ID) in adult murine ventricle. As a point of comparison, we characterized the ultrastructure of the ID in mice heterozygous-null for the desmosomal gene plakophilin-2 (PKP2; mice dubbed PKP2-Hz). METHODS AND RESULTS: Tomographic EM images of thin sections of adult mouse ventricular tissue were processed by image segmentation analysis. Novel morphometric routines allowed us to generate the first quantitative description of the ID intercellular space based on three-dimensional data. We show that complex invaginations of the cell membrane significantly increased the total ID surface area. In addition, PKP2-Hz samples showed increased average intercellular spacing, ID surface area, and membrane tortuosity, as well as reduced number and length of mechanical junctions compared with control. Finally, we observed membranous structures reminiscent of junctional sarcoplasmic reticulum at the ID, which were significantly more abundant in PKP2-Hz hearts. CONCLUSION: We have developed a systematic method to characterize the ultrastructure of the intercellular space in the adult murine ventricle and have provided a quantitative description of the structure of the intercellular membranes and of the intercellular space. We further show that PKP2 deficiency associates with ultrastructural defects. The possible importance of the intercellular space in cardiac behaviour is discussed.